2020
DOI: 10.3390/molecules25071547
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Amine Formation in Grilled Chicken Depending on Body Parts and Treatment Conditions

Abstract: Heterocyclic amines (HCAs) carcinogenicity is known since the 1970′s, but the exact way of their formation is still unclear. During these examinations different body parts (breast filet with and without skin, thigh filet without skin and full wing with skin) of chickens from the same Ross 308 strain were analyzed after grilling with the combination of 3-3 temperature and duration levels (150-180-210 °C and 2.5-5-10 min per side). Five different kinds of heterocyclic amines (HAR, NOR, MeIQx, 4,8-DiMeIQx and PhI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Moisture and ash content of raw samples were found as 72.09 ± 0.61% and 1.04 ± 0.07%, respectively. The compositions of the raw samples were compatible with previous reports (Pleva et al, 2020; Tengilimoglu‐Metin et al, 2017; Tengilimoglu‐Metin & Kizil, 2017). These parameters significantly changed after the cooking process.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Moisture and ash content of raw samples were found as 72.09 ± 0.61% and 1.04 ± 0.07%, respectively. The compositions of the raw samples were compatible with previous reports (Pleva et al, 2020; Tengilimoglu‐Metin et al, 2017; Tengilimoglu‐Metin & Kizil, 2017). These parameters significantly changed after the cooking process.…”
Section: Resultssupporting
confidence: 91%
“…In the present study, MeIQx did not form in any samples cooked at 150°C, while 0.07 ng/g MeIQx formed at control samples cooked at 200°C. Similarly, Pleva et al (2020) reported that MeIQx levels of chicken thigh samples grilled at 150 and 180°C for 5 or 10 min per side were under detection limits. In this study, addition of VME prevented the formation of MeIQx at 200°C.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…They are easily absorbable in the gastrointestinal tract, and an arilnitrenium ion is formed as a result of the reaction with cytochrome P450monoaminooxidase, which intensifies neoplastic-increasing processes during DNA replication. As presented by Plevaet et al [ 40 ] in experiments of animals, they contributed to the formation of benign neoplastic lesions of liver and malignant ones in the large intestine.…”
Section: Poultry Meat Spoilage and Biogenic Amine Contentmentioning
confidence: 94%
“…It further results in smooth-muscle contraction, resulting in diarrhoea, vomiting, and stomach-ache [ 16 , 38 , 39 ]. Histamine is strictly related to fish and fish product poisoning, but it also occurs in poultry meat, particularly during poultry meat processing in high temperatures and meat with skin processing [ 38 , 40 ]…”
Section: Poultry Meat Spoilage and Biogenic Amine Contentmentioning
confidence: 99%